Experimental evaluation and qualitative increase of thermal load in open refrigerated display cases due to breakage of the air curtain - Nascimento, Samuel Mariano do (2013)
Open refrigerated display cabinets are used extensively in convenience stores and supermarkets in order to display perishable products meeting the criteria of food security. In Brazil, there are about 81 thousand stores using open or closed refrigerated display cabinets for products sale. The vertical open refrigerated display cabinet is the model that consumes more energy. About 81% its total consumption is due to the infiltration of outside air through the air curtain. The air curtain performance can be influenced by several factors, among which, the customers’ movement near the equipment frontal opening causing a perturbation in the air jet and increasing its energy consumption. Experimental tests were conducted in open and closed hours of a food store. The TEF increases by 22% and cooling load by 18% when the shop is open. The results comparison allows evaluating the thermal performance of the equipment among test cases for a real scenario.